Complete guide to prescription & nonprescription drugs, 2011 - Griffith, H. Winter (Henry Winter), 1926-1993.; Moore, Stephen W.; Boesen, Kevin; Boesen, Cindy (New York : Penquin Group, 2010)
Covers more than six thousand drugs with revised drug charts, information about new drugs approved by the FDA, directions, and restrictions.
"Includes: revised information on new FDA changes; easy-to-use chart format for quick access to data; information on dangerous interactions and side effects; warnings and vital data for safe use; comprehensive coverage of lifestyle drugs - skin aging, obesity, sexual dysfunction, and more; more than 6,000 brand names and 1000 generic names"--Cover.
"A Perigee book"
Includes index.
Keywords: Drugs; Drugs, Nonprescription